A change in the start reaction time distribution of the past five World Championships in athletics by the false start rule revision - Yokokura, S.; Kajiwara, Y.; Ono, S. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
In short-distance races of international alhletic meets such as the World Championships in Athletics, the use of false start apparatuses is now required (International Association of Athletics Federations: IAAF Rules No. 1, Clause 1 a-c). In January, 2003, the IAAF applied a new rule, "...only one false start per race shall be allowed without the disqualification of the athlete(s) making the false start. Any athlete(s) making further false starts in the race shall be disqualified (IAAF Rules No. 162)." The effects of this change on the start reaction time are studied here by comparing the past five IAAF World Championships in Athletics games.